2013
DOI: 10.7438/1584-9341-9-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Colonic and Gastric Metastasis of Endometrial Adenocarcinoma - Case Report

Abstract: MULTIPLE COLONIC AND GASTRIC METASTASIS OF ENDOMETRIAL ADENOCARCINOMA -CASE REPORT (Abstract): INTRODUCTION:In the gynecological malignancies endometrial adenocarcinoma is the second most common, giving early hematogenous and lymphatic metastasis to the lungs, brain and bones. CASE REPORT: We present the case of a 71 year old patient who underwent surgery two years ago for endometrial adenocarcinoma and followed postoperatively multimodal oncological treatment. The patient was admitted in January 2013 in the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Although the most frequent location of metastasis from endometrial adenocarcinoma is at the lymph node level (48%), recurrence at the vagina (42%), lung (24%), and peritoneum (27%) is also common. The hematogenous or lymphatic route is responsible for them [ 2 , 5 ]. The location of metastases in the digestive tract is uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Although the most frequent location of metastasis from endometrial adenocarcinoma is at the lymph node level (48%), recurrence at the vagina (42%), lung (24%), and peritoneum (27%) is also common. The hematogenous or lymphatic route is responsible for them [ 2 , 5 ]. The location of metastases in the digestive tract is uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, only 3 similar cases have been published in the literature. 2 , 3 , 5 Endometrial adenocarcinoma is the most common histologic subtype of endometrial cancer. The metastasis is mainly via lymphatic and hematogenous modes.…”
Section: Discussionmentioning
confidence: 99%
“…Molnar et al published a case of a 71-year-old female with a past history of endometrial adenocarcinoma status postsurgical resection who presented with anemia and bowel obstruction symptoms 2 years after the surgery. 5 By imaging and endoscopic evaluation, she was found to have a tumor invading the left colon as well as spleen and gastric antrum. She underwent left hemicolectomy, splenectomy, and distal gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Jauregui et al 12 reported a case of disease recurrence of stage 3b endometrial cancer to the sigmoid colon 1 month after TAH-BSO, in an 89-year-old who presented with haematochezia. Finally, Molnar et al 13 presented a case of a 71-year-old who presented with sub-occlusive syndrome, weight loss and anemia, found to have recurrence of stage 3b serous endometrial cancer 2 years status post-surgical management and adjuvant chemoradiotherapy. Intraoperatively, she was found to have multiple metastatic lesions in the colon (ascending, transverse and descending) and the gastric antrum (with invasion of the lower pole of spleen).…”
Section: Case History/ Examinationmentioning
confidence: 99%